2012
DOI: 10.1111/j.1469-8137.2012.04346.x
|View full text |Cite
|
Sign up to set email alerts
|

The susceptibility of soil enzymes to inhibition by leaf litter tannins is dependent on the tannin chemistry, enzyme class and vegetation history

Abstract: SummaryBy inhibiting soil enzymes, tannins play an important role in soil carbon (C) and nitrogen (N) mineralization. The role of tannin chemistry in this inhibitory process, in conjunction with enzyme classes and isoforms, is less well understood.Here, we compared the inhibition efficiencies of mixed tannins (MTs, mostly limited to angiosperms) and condensed tannins (CTs, produced mostly by gymnosperms) against the potential activity of b-glucosidase (BG), N-acetyl-glucosaminidase (NAG), and peroxidase in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 68 publications
1
50
0
Order By: Relevance
“…In present study, colophony and abietic acid showed a correlation between the decrease in activity and the precipitation of an enzyme. A similar mechanism was already shown for tannins, which inhibit enzymes by creation of complexes with them (Schimel et al, 1998;Adamczyk et al, 2009;Triebwasser et al, 2012); however, sometimes only minor decrease in activity was observed after complexation (Juntheikki and Julkunen-Tiitto, 2000).…”
Section: Discussionmentioning
confidence: 54%
“…In present study, colophony and abietic acid showed a correlation between the decrease in activity and the precipitation of an enzyme. A similar mechanism was already shown for tannins, which inhibit enzymes by creation of complexes with them (Schimel et al, 1998;Adamczyk et al, 2009;Triebwasser et al, 2012); however, sometimes only minor decrease in activity was observed after complexation (Juntheikki and Julkunen-Tiitto, 2000).…”
Section: Discussionmentioning
confidence: 54%
“…Along with the total quantity of tannins, climate influenced both the monomer composition and mean degree of polymerization of tannins, the two parameters that are seldom investigated despite their regulatory influence on the potential biological reactivity of tannins (Zucker, 1983; Kraus et al, 2003b; Tharayil et al, 2011; Triebwasser et al, 2012). Reactivity of CT is a function of the hydroxylation pattern of the B-ring, and tannins with trihydroxy B-rings (PD) are more reactive than those with dihydroxy B-ring (PC).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the greater chain-length and higher proportion of PC units would have resulted in lower extractability of tannins from the leaf tissues, resulting in the observed lower content of tannins in Wet treatments. Also, the Wet treatments, despite a lower content of CTs, have a higher percentage of HTs, which have a higher enzyme inhibition capacity compared to CTs (Triebwasser et al, 2012). Thus, overall, the leaves formed under Wet treatments would have a similar herbivore deterrence contributed by tannins, despite a lower content of CTs in the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations